Fauna Aquatic Insects in the Sewage Stabilization Ponds of Kashan University of Medical Sciences - Rooholah Dehghani (آب و فاضلاب, 2007)
Stabilization pond is a sewage treatment method. Being rich in organic matter, sewage is a favorable habitat for a variety of aquatic insects. Given the importance of these insects in the organic transformation cycle, this stabilization was carried out in 2005 in order to identify the aquatic insects living in the stabilization ponds ofKashanUniversityof Medical Sciences. For the purposes of this descriptive study, 9 series of sampling were performed and 1032 of larva, nymphs, and adults were collected from the four corners of each pond and sent to the laboratory for identification. The samples were identified using stereo-microscope and morphological identification keys. The species identified included Diptera (52%), Hempitera (24%), Ciclopodidade (12%), Hydroacarina (9.5%), Coleptera (0.77%), Aranida (0.67%), Hymenoptera (0.58%), and Odonata (0.48%). The families identified in the samples from the stabilization ponds under study involved Chironomidae and  Culicidae from the Diptera order; Corixidae, Notonectidae, Cupepodae, and Copepodidae from the order Hemiptera; Hydrophilidae from the order Coleptera; Aranidae from the order Aranida; Vospidae from the order Hymenoptera; and Ashnidae the order Odonata.